Automatic Garlic Peeling Machine Design and Performance Evaluation: Desain dan Evaluasi Kinerja Alat Pengupas Kulit Bawang Putih Otomatis - Achmad Basori; Mulyadi (Academia Open, 2023)
General Background the increasing demand for automation in the food processing industry requires the development of efficient technologies that can enhance productivity and ensure food safety. Specific Background the peeling of garlic is a time-consuming and labor-intensive process, often leading to contamination, thus highlighting the need for innovative solutions in garlic processing. Knowledge Gap existing peeling methods are less automated, creating a gap in the availability of efficient technology for garlic peeling that maintains hygiene standards. Aims this research aims to design and develop an automatic garlic peeler that effectively integrates mechanical, pneumatic, and electrical components to optimize the peeling process. Results experimental findings show that at a minimum pressure of 1 bar, this tool can peel an average of 28.6 grams of garlic from 812 grams, while at a maximum pressure of 5 bars, it can peel 240.6 grams. PNovelty the use of stainless steel 316 in the design provides corrosion resistance, ensuring food safety during the peeling process, which is a new approach in the context of automatic food processing technology. Implications this research contributes to advancements in food processing automation, offering insights into the integration of pneumatic systems that can enhance efficiency in culinary practices and improve hygiene standards in food handling. Highlights: The design integrates mechanical, pneumatic, and electrical components for optimal performance. Peak peeling efficiency achieved at 4 bar pressure, processing 241.3 grams of garlic in 15 seconds. Use of stainless steel 316 ensures corrosion resistance and maintains food safety standards. Keywords: Automatic Peeler, Garlic Processing, Pneumatic System, Food Safety, Efficiency